Yeast as a Model System to Study Tau Biology. (2011) - De Vos, Ann; Anandhakumar, Jayamani; Van den Brande, Jeff; Verduyckt, Mathias; Franssens, Vanessa; Winderickx, Joris; Swinnen, Erwin
Abstract : Hyperphosphorylated and aggregated human protein tau constitutes a hallmark of a multitude of neurodegenerative diseases called tauopathies, exemplified by Alzheimer's disease. In spite of an enormous amount of research performed on tau biology, several crucial questions concerning the mechanisms of tau toxicity remain unanswered. In this paper we will highlight some of the processes involved in tau biology and pathology, focusing on tau phosphorylation and the interplay with oxidative stress. In addition, we will introduce the development of a human tau-expressing yeast model, and discuss some crucial results obtained in this model, highlighting its potential in the elucidation of cellular processes leading to tau toxicity.